2018
DOI: 10.2134/agronj2017.10.0578
|View full text |Cite
|
Sign up to set email alerts
|

Crop Diversification Strategy to Improve Economic Value in Brazilian Sugarcane Production

Abstract: Core Ideas The authors evaluated economically different treatments for sugarcane renewal. The authors present the impact of the diversification on sugarcane production on venture risk. The authors used the real options theory with a polynomial approach to model the managerial flexibility in exchanging sugarcane with soybean. Crop diversity is beneficial to rural properties in terms of reducing business risks and increasing agricultural revenues. In sugarcane (Saccharum spp) farming, crop diversity using rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Our results are in line with those of Farinelli et al, 53 who pointed to evidence of the benefits of planting diversification between sugarcane and soybeans on a rural property in the region of Jaboticabal, São Paulo, Brazil. Adequate planting flexibility between both would tend to minimize risk and increase revenue.…”
Section: Data and Empirical Resultssupporting
confidence: 93%
“…Our results are in line with those of Farinelli et al, 53 who pointed to evidence of the benefits of planting diversification between sugarcane and soybeans on a rural property in the region of Jaboticabal, São Paulo, Brazil. Adequate planting flexibility between both would tend to minimize risk and increase revenue.…”
Section: Data and Empirical Resultssupporting
confidence: 93%
“…Some authors show that diversity in farming activities may increase income stability and reduce the income risks of resource-poor households (Farinelli et al 2018;Niehof 2004;Pacin and Oesterheld 2014). However, beyond comparing mixed and specialized systems, some authors have shown that, as in the present study, the organization of activities provided by farm practices can lead to an impact on farm sustainability performances, such as vulnerability, within-farm interactions, and self-sufficiency (Lin 2011;Martin and Magne 2015;Sneessens et al 2016;Stark et al 2016).…”
Section: Diversity and Sustainability In Agricultural Systemsmentioning
confidence: 50%
“…The impact of various diversity measures is assessed on a large panel of economic, production, and environmental performances but rarely in the same study. For instance, the impact of farm diversity is assessed on the ability of systems to maintain food autonomy (Martin and Magne 2015), to maintain a level of ecosystem service delivery (Sanderson et al 2013), to allow flexibility (Rippol-Bosch et al 2017), or to withstand weather or economic hazards (reflected in biomass growth variability (Martin and Magne 2015) or on business indicators (Farinelli et al 2018)). In this study, we chose to work on a set of performances at both the farm and territory scales.…”
Section: Importance Of Considering a Set Of Performances To Assess The Impact Of Diversitymentioning
confidence: 99%
“…In this study, we calculated the free cash flow (FCF) to allow the flow structure to be adapted to the Brazilian tax context (Faleiros et al, 2018, Farinelli et al, 2018. The operational and productive parameters and market information were used to construct cash flow variables.…”
Section: Economic Analysesmentioning
confidence: 99%
“…The operational and productive parameters and market information were used to construct cash flow variables. The study extrapolated the results to a 75 ha-property, which is the modal profile of the study region (Faleiros et al, 2018;Farinelli et al, 2018). The study controlled for uncertainties in price and productivity of corn and beef using the Monte Carlo simulation, considering 10,000 possibilities for each production system (Oliveira and Medeiros Neto, 2012), and the assumptions regarding the volatility of these variables (Table 1).…”
Section: Economic Analysesmentioning
confidence: 99%